Roles and Responsibilities Relating Land Agreement Official of Liability Provision of Rights With Mudharabah in Islamic Bank - Yoni Oktaviani; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
This research examines the concept of binding guarantee of the rights to land in accordance with laws and regulations in Indonesia and Islamic law; as well as the roles and responsibilities associated with APHT PPAT in the contract of Mudharabah in Islamic Bank. The method used in this research is normative. The results showed that APHT can not be used on the contract of Mudharabah and Islamic law has its own security institutions, namely Rahn. Roles and responsibilities of PPAT associated with APHT in the contract of Mudharabah in Islamic Bank will be explained by Act No. 4 of 1996, Act No. 21 of 2008, Government Regulation No. 37 of 1998, as amended by Regulation No. 24 of 2016, PERKABAN No. 1 of 2006, as amended by PERKABAN No. 23 of 2009 and Theory of Accountability.Keywords: Responsibility; Land Agreement Official; Mudharabah System.